A Distributed Framework for Programming the Artificial Intelligence of Mobile Robots in Smart Manufacturing Systems - Naidoo, Nicol; Bright, Glen; Stopforth, Riaan (2019 Southern African Universities Power Engineering Conference/Robotics and Mechatronics/Pattern Recognition Association of South Africa (SAUPEC/RobMech/PRASA), 2019)
Mobile robots have provided solutions for materials handling operations in Advanced Manufacturing Systems. The smart manufacturing system of today relies on intelligent machines, devices and logistics integration to meet the challenges of consumer demands and mass customization. Machine (or robot) integration allows data access of high level supply chain silos. This provides for intelligent, machine programming that expedites processes to meet the change in consumer demands. The motivation of the research study was based around the consumer market and the Fourth Industrial Revolution, Industry 4.0. The paper discusses the design, development and example of a framework for the robotic automation industry. The feature of the framework is distributive in architecture. This meets some of the challenges and requirements for a smart manufacturing system.